Efficiently Searching for Close-in Companions Around Young M Dwarfs Using a Multiyear PSF Library - Aniket Sanghi; Jerry W. Xuan; Jason J. Wang; Dimitri Mawet; Brendan P. Bowler; Henry Ngo; Marta L. Bryan; Garreth Ruane; Olivier Absil; Elsa Huby (The Astronomical Journal, 2024)
We present Super-RDI, a unique framework for the application of reference star differential imaging (RDI) to Keck/NIRC2 high-contrast imaging observations with the vortex coronagraph. Super-RDI combines frame selection and signal-to-noise ratio (S/N) optimization techniques with a large multiyear reference point-spread function (PSF) library to achieve optimal PSF subtraction at small angular separations. We compile an ∼7000 frame reference PSF library based on a set of 288 new Keck/NIRC2 $L^{′} $ sequences of 237 unique targets acquired between 2015 and 2019 as part of two planet-search programs designed for RDI, one focusing on nearby young M dwarfs and the other targeting members of the Taurus star-forming region. For our data set, synthetic companion injection-recovery tests reveal that frame selection with the mean-squared error metric combined with Karhunen–Loève Image-Processing-based PSF subtraction using 1000–3000 frames and ≲500 principal components yields the highest average S/N for injected synthetic companions. We uniformly reduce targets in the young M-star survey with both Super-RDI and angular differential imaging (ADI). For the typical parallactic angle rotation of our data set (∼10°), Super-RDI performs better than a widely used implementation of ADI-based PSF subtraction at separations ≲0.″4 (≈5 λ / D ), gaining an average of 0.25 mag in contrast at 0.″25 and 0.4 mag in contrast at 0.″15. This represents a performance improvement in separation space over RDI with single-night reference star observations (∼100 frame PSF libraries) applied to a similar Keck/NIRC2 data set in previous work. We recover two known brown dwarf companions and provide detection limits for 155 targets in the young M-star survey. Our results demonstrate that increasing the PSF library size with careful selection of reference frames can improve the performance of RDI with the Keck/NIRC2 vortex coronagraph in $L^{′} $ .